1977
DOI: 10.1007/bf00426599
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol effects on acute marihuana intoxication in man

Abstract: To investigate the possible interaction of a beta adrenergic blocking agent and marihuana, six healthy experienced marihuana smokers received the two drugs separately and in combination. Propranolol (120 mg per os) reduced resting HR and BP; there were no changes in performance on tasks designed to test psychomotor speed, attention, memory and learning. Marihuana (10 mg delta9-THC), administered in smoke, induced the typical subjective state ("high") with marked increases in HR, BP and conjunctival injection; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The beta-adrenergic blocking agent propranolol causes mild sedation, but pretreatment with propranolol blocked cannabis-induced cardiovascular effects and learning impairment in a small clinical trial [118].…”
Section: Resultsmentioning
confidence: 92%
“…The beta-adrenergic blocking agent propranolol causes mild sedation, but pretreatment with propranolol blocked cannabis-induced cardiovascular effects and learning impairment in a small clinical trial [118].…”
Section: Resultsmentioning
confidence: 92%
“…14' Propranolol has been reported to prevent marijuana-induced tachycardia, and it appeared, in addition, to prevent the learning impairment produced by this drug, but this requires confirmation. 142 In a placebo-controlled trial, propranolol was of no value in helping cigarette smokers to stop A single psychotic patient with recurrent life-threatening water intoxication secondary to compulsive water drinking responded well to 1 g of propranolol daily, but it is difficult to be certain whether this reflected an antipsychotic action rather than a specific effect on her drinking b e h a~i 0 r . I~~…”
Section: E Other Conditionsmentioning
confidence: 99%
“…Taken together, the effects of manipulating the endocannabinoid system and modulating noradrenergic transmission suggest that the two systems may interact or share some common signaling pathways. Consistent with this, a study performed in human subjects revealed that administration of the β-AR blocker, propranolol, before consumption of marijuana prevented cannabinoid-induced cardiovascular effects and prevented cannabinoid-induced learning impairment (Sulkowski et al , 1977). In agreement with this, early anatomical studies using autoradiography have identified moderate CB1r binding and CB1r mRNA in the principal noradrenergic nuclei, the LC and NTS (Herkenham et al , 1991; Mailleux & Vanderhaeghen, 1992; Matsuda et al , 1993; Derbenev et al , 2004; Jelsing et al , 2008).…”
Section: The Interplay Between the Endocannabinoid And Noradrenergmentioning
confidence: 62%